IMPROVING MATHEMATICAL COMPETENCE IN PRIMARY SCHOOL TO ENABLE SKILL TRANSFERS IN NEW SITUATIONS - Sondore, Anita; Krastiņa, Elfrīda; Drelinga, Elga; Daugulis, Pēteris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Mathematical competence is one of the basic competences defined in the EU. Results of international studies in recent years show that the percentage of pupils in Latvia with high level (5.,6.) of mathematical competence has decreased from 8% (PISA, 2012) to 5,2% (PISA, 2015). Observations of mathematical lessons show that individualization of studies is not a popular everyday feature, nonstandard problems are rarely used in the work with primary school pupils. Sustainable education can not be envisioned without creative thinking necessary for solving various nonstandard problems. Mathematical competitions also require creative applications of knowledge. The goal of this study was to analyze problems of Latvian mathematical contests for grades 4-6 of the last 3 years according to categories of mathematical content. The most important cognitive and metacognitive strategies necessary for their solution are shown. It is important to turn attention of teachers to much wider inclusion of contest problems into study process of primary school. It will enable to individualize studies and stimulate skill transfer to new situations for gifted pupils. The authors encourage teachers to use nonstandard (contest) problems as an indivisualization tool which will give opportunity for pupils to master knowledge and skill transfer. It will provide regular training of mind and positive emotions for pupils who are bored with solving standard problems.